(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Successful entrepreneurs are usually modeled ascombinations of different skills. The article is aimed at the impact ofentrepreneurial skills promoting entrepreneurship among young people. Theresults find out and confirmed that the main factors of entrepreneurialintention are technical skills, business management skills, and entrepreneurialskills. Innovation and others are personality traits, attitude towardsentrepreneurship, behavioral control, and they can be developed during thestudy process.